(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2012)
Pregnancy in patients with systemic lupus erythematosus is associated with a high risk of maternal disease exacerbation and adverse fetal outcome. This review summarizes recent published findings on lupus pregnancy. Literature review: The literature has profound agreement on thefact that, for most women with inactive and stable systemic lups erythematousus, pregnancy is safe for both mother and fetus. The main risk factors for adverse pregnancy course and outcome are active disease, nephritis with proteinuria, hypertension and maternal serum antibodies to SS-A/Ro, SS-B/La, cardiolipin, 2-glycoprotein I, and lupus anticoagulant. Recent studies have broadened our understanding of the immunological mechanism underlying congenital heart block induced by anti-Ro/La antibodies. Pregnancy in patients with systemic lupus erythematosus is safe and manageable provided the disease is stable. Patients should be closely followed up before pregnancy for pregestational risk factors and should get extra attention during gregnancy. The disease can be safely managed in some cases of lupus flare during pregnancy. JCMCTA 2012; 23(1): 53-56